Causes of financial distress: The case of syariah compliant companies / Marliyana Mohtar - Mohtar, Marliyana (2007)
Financial distress, in general term used to indicate a condition when promises to creditors of a company are broken or honored with difficulty. Sometimes financial distress can lead to bankruptcy. Based on previous study, Amy Kam (2005) state that financial distress in China is caused by poor operating, not by leverage. So, this paper examines the causes of financial distress in Malaysia. Samples of 98 distressed firms are taken in this study. In order to locate firms in financial distress, firstly we need to analyze all the listed Syariah compliant firms of Main and Second Board of Bursa Malaysia over the period of 2000 to 2002. A firm is identified as having suffered from financial distress when the interest cover is less than 1. From the sample of 98 distressed firms, method of Logistic Regression is employed in this study to examine the causes of financial distress. The expected finding of this study, financial distress is caused by poor operating, not by leverage.